ANALYSIS OF CONDENSER PERFORMANCE DESALINATION OF SOLAR ENERGY OF THE NATURAL VACUUM SYSTEM AT THE TIME OF LOW RADIATION INTENSITY - Himsar Ambarita; Eko Yohanes Setiawan (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2018)
Natural desalination device solar vacuum system has a main component of evaporator, condenser, and solar collector. The production of clean water from this appliance is strongly influenced by the performance of the condenser.On this research, condenser performance is performed when the intensity of solar radiation is low. The measurement data for 2 days when the sky is not bright is used to perform the condenser performance analysis. The result of analysis on the first day was found that the working energy of condensorsirippada was 141 J / day, while if without 29 J / day fins. So that the effectiveness of fins of 112 J / day. While on the second day found heat transfer using 122 J / day fins without fins 25 J / day to obtain fin effectiveness of 97 J / day. This is very influential on clean water production. The condensate rate on the 1st day is highest at 0.00018 kg / min, with an average of one day experiment 0.0001 kg / min, yielding fresh water of 0.8 Liter. On the 2nd day the highest condensate rate is 0.00019 kg / min with an average of condensate rate for one day 0.00011 kg / min, yielding fresh water of 0.81 Liter.